The Impact of Viral Marketing, Influencer Marketing and Celebrity Endorsers on purchasing decisions at Blibli E-commerce: Study of students in Indonesia - Muhammad Roby Jatmiko; Fiderius Ismanto; Nuruddin Mahmud; Bayu Teguh Wibowo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The phenomenon captured in this research is that in the top brand index from 2019 to 2023, Blibli is the e-commerce with the lowest top brand index. The aim of this research was to identify the influence of Viral Marketing, Influencer Marketing and Celebrity Endorsers on purchasing decisions at Blibli E-commerce. The respondents in this research were Indonesian students totaling 200 respondents, using purposive sampling data collection techniques. data processed with SPSS. The results of data processing show that, Viral Marketing, Influencer Marketing and Celebrity Endorsers have a positive and significant influence on purchasing decisions at Blibli E-commerce made by Indonesian students. The interesting thing in this research is that Indonesian students decide to buy products at Blibli because of celebrities. The endorser is Yura. This is because the communication style provided by Yura as a celebrity endorser is very attractive and convincing to Indonesian students.